Rozwiązywanie równań : -2(-2x+4) = - (-2x-6) 4x+6 = 8x+9 jedna druga x + jedna czwarta = jedna druga (4x-6) 2(3x-6) = -4(-2x+8) 6 ( -2x+4) = -3 ( -2x+6)
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
-2[-2x+4]=-[-2x-6]
4x-8=2x+6
4x-2x=6+8
2x=14 /:2
x=7
4x+6=8x+9
4x-8x=9-6
-4x=3 /:-4
x= -3/4
1/2x+1/4=1/2[4x-6] /*4
2x+1=8x-12
2x-8x= -12-1
-6x=- 13 /:-6
x=13/6
x=2 1/6
2[3x-6]= -4[-2x+8]
6x-12=8x-32
6x-8x= -32+12
-2x= -20 /:-2
x=10
6[-2x+4]= -3[-2x+6]
-12x+24=6x-18
-12x-6x= -18-24
-18x= -42 /:-18
x=42/18
x=2 6/18
x=2 1/3